-2x(-8)x(-6)=

Simple and best practice solution for -2x(-8)x(-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x(-8)x(-6)= equation:


Simplifying
-2x(-8) * x(-6) = 0

Reorder the terms for easier multiplication:
-2 * -8 * -6x * x = 0

Multiply -2 * -8
16 * -6x * x = 0

Multiply 16 * -6
-96x * x = 0

Multiply x * x
-96x2 = 0

Solving
-96x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-96'.
x2 = 0

Simplifying
x2 = 0

Take the square root of each side:
x = {0}

See similar equations:

| 67-1/2= | | -13x-152=127-4x | | -9+5-(-4)-8= | | 7-K=-5 | | 6/7-1/2= | | (0.32)(-1.4)= | | -305-4x=5x+127 | | x*x=7.7 | | -23-5-(-14)= | | -10x-68=86-17x | | 3x+9=.5 | | x+(-x)=18 | | 7+x+(-x)=18 | | 3(x-1)-3(x+4)=0 | | -49=2(4-3s) | | 5=10X+1Y | | 3b+5=20-b | | -5(6x-2)+4=-30x+14 | | 4/15x10/12 | | 1/0n | | 400x-170x-820000=400x-200x-7000000 | | 0/0Y | | x^2=-8+6i | | -3y=-5x-6 | | (6X^2+11)(9X^3-4)= | | 3X+4-7=14x | | 9x+11=46-2x | | 12/5×7/8 | | 4x+8x=3x+14 | | Y=1nx+5 | | 3(3+5)-(4-3x)=29 | | X^3-2x^2-4=1 |

Equations solver categories